Politik Dinasti Di Indonesia : Tinjauan Kritis Terhadap Penerapan Demokrasi Di Era Kepemimpinan Presiden Jokowi - Asitha Dewi Mustika Syanur; Ida Bagus Shantih A. W.; Lucy Afrilia (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
The aim of the research is to reveal dynastic politics and the implementation of democracy in the era of President Jokowi's leadership. The 1945 Constitution of the Republic of Indonesia, explicitly recognizes that the form of the Unitary State of the Republic of Indonesia adopts a democratic system. In reality, dynastic politics or political dynasties have developed and are considered a violation of democratic ethics in Indonesia. All efforts and strategies made by the ruling parties to assign positions based on "family ties" can hinder and complicate public participation in political contestation in democratic countries. The development of dynastic political issues in the era of President Jokowi's leadership began with the advancement of President Jokowi's son-in-law and eldest son to become Mayor. Then there was a decision by the Constitutional Court which was deemed to have violated the code of ethics regarding changes to the minimum requirements for presidential and vice presidential candidates for the Republic of Indonesia which succeeded in bringing Gibran Rakabuming as a candidate for vice president of the Republic of Indonesia. This alleged dynastic politics has raised concerns regarding its impact on the political process, public representation, and the democratic system in Indonesia. It is important to reform the political recruitment process so that it is more transparent, has integrity, and is based on individual qualifications and capabilities. This will not only strengthen political parties as democratic institutions but will also maintain the sustainability and stability of democracy in Indonesia.